Non-executive employee stock options and corporate innovation - Chang, Xin (2015)
We provide empirical evidence on the positive effect of non-executive employee stock options on corporate innovation. The positive effect is more pronounced when employees are more important for innovation, when free-riding among employees is weaker, when options are granted broadly to most employees, when the average expiration period of options is longer, and when employee stock ownership is lower. Further analysis reveals that employee stock options foster innovation mainly through the risk-taking incentive, rather than the performance-based incentive created by stock options.